PELATIHAN SENAM AEROBIK UNTUK MENINGKATKAN KEBUGARAN JASMANI MASYARAKAT DI DESA CIBUNTU - Maharani, Widya; Shabah, Musyaffa Amin Ash; Haqiyah, Aridhotul (Universitas Islam 45 Bekasi, 2025)
A healthy lifestyle has become an essential need in modern society as it improves the quality of life while preventing various degenerative diseases. The main problem faced by the community in Cibuntu Village is the lack of awareness regarding the importance of regular physical activity as an effort to maintain physical fitness and mental health. To address this issue, a community service program was carried out in the form of a healthy aerobic exercise activity designed as a medium for health education and the cultivation of active lifestyle habits. The implementation method included counseling on the benefits of aerobic exercise, demonstrations of easy-to-follow movements, and direct assistance to enable participants to practice independently. The results showed high enthusiasm from the community, reflected in active participation in each exercise session, improved understanding of the importance of regular exercise, and changes in habits toward a healthier lifestyle. This activity not only had a positive impact on physical fitness but also contributed to improving participants’ motivation, self-confidence, and psychological well-being. Therefore, the healthy aerobic exercise program in Cibuntu Village can be concluded to have successfully raised community awareness to sustainably adopt a healthy lifestyle as an effort to maintain health and quality of life.